ARTISTIC EDUCATION AND MUSEUMS IN A GENDER KEY: LEARNING SPACES AND VISUAL IMAGINARIES UNDER CONSTRUCTION (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
This article proposes a reflection on museums as learning spaces derived from research that seeks to understand their didactic potential within the framework of a university training practice carried out in collaboration with the Andalusian Center for Contemporary Art (CAAC) in 2024, motivated by the exhibition Malgorzata Mirga-Tas. Remembrance and resignification. The itinerary followed tried to offer guidance to the students of the MAES of the University of Seville that would facilitate the interpretation of the creations of the artist and activist Malgorzata Mirga-Tas, under which lies a marked political and feminist background. After evaluating the museum experience, attention will be focused on assessing its impact.
Keywords: Museums; Artistic education; Contemporary Art; gender; feminism